Noms généraux et noms sous-spécifiés : des relations à préciser - Richard Huyghe (Corela)
The aim of this article is to examine the notion of semantic underspecification through the different interpretations it has been given in existing works. In the nominal domain, two properties are associated with underspecification: semantic generality on the one hand, and the ability to encapsulate propositional contents on the other. These properties distinguish two nominal classes, the definition of which is analyzed. The class of general nouns is characterized by unclear delimitation and heterogeneity: at least three subtypes can be distinguished. The class of propositional encapsulation nouns (i.e. ‘shell nouns’) can be defined and partitioned according to the distribution with different types of clauses in different syntactic configurations. The functional properties of both classes and their intersection are finally examined.